Media in Malaysia's 1999 general election / Dr. Halimahton Shaari, Dr. Kiranjit Kaur and Dr. Sankaran Ramanathan - Shaari, Halimahton (Dr.); Kaur, Kiranjit (Dr.); Ramanathan, Sankaran (Dr.) (Faculty of Communication and Media Studies (FCMS), 2004)
Regardless of whether they are mass or interpersonal, media in Malaysia generally reflect the various sub-systems of the multi-racial, mulyi-linguistic and multi-ethnic society that exist and operate in the country.